2014
DOI: 10.1136/vr.102196
|View full text |Cite
|
Sign up to set email alerts
|

Angiostrongylus vasorum in Great Britain: a nationwide postal questionnaire survey of veterinary practices

Abstract: The lungworm, Angiostrongylus vasorum, was first reported in indigenous dogs in southwestern England in 1980 and has since been recorded in Wales, southeastern England and, more recently, in the West Midlands, northern England and Scotland. The nationwide distribution of the parasite was evaluated using a postal questionnaire sent to 3950 small animal practices during 2009. Information was sought on the location of each practice, awareness of the parasite locally, number of cases diagnosed over the past year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(41 reference statements)
2
30
0
Order By: Relevance
“…The parasite is now widespread in central England, with clusters in the south-east of England and the south of Wales and a patchy distribution in northern England and Scotland. There is no longer an endemic focus in the south-west of England, as the authors found within a national questionnaire survey of 1419 veterinary practices (Kirk et al 2014). After the first detection of A. vasorum in British foxes in Cornwall (Simpson 1996), 546 red foxes were studied by Morgan et al (2008), showing an overall prevalence of 7.3 % in the UK that varied from 0 % in Scotland and northern England to 23.2 % in south-east England.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The parasite is now widespread in central England, with clusters in the south-east of England and the south of Wales and a patchy distribution in northern England and Scotland. There is no longer an endemic focus in the south-west of England, as the authors found within a national questionnaire survey of 1419 veterinary practices (Kirk et al 2014). After the first detection of A. vasorum in British foxes in Cornwall (Simpson 1996), 546 red foxes were studied by Morgan et al (2008), showing an overall prevalence of 7.3 % in the UK that varied from 0 % in Scotland and northern England to 23.2 % in south-east England.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that A. vasorum is abundant in foxes (n = 70) from the Copenhagen area with a prevalence of 80 %, but not in foxes (n = 48) from Southern Jutland (Al-Sabi et al 2014). A lot of research is also done in the UK, which harbours some highly endemic foci and where A. vasorum has spread beyond traditional endemic areas (Blehaut et al 2014;Kirk et al 2014). The parasite is now widespread in central England, with clusters in the south-east of England and the south of Wales and a patchy distribution in northern England and Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…By entering test results online and pooling data (such as at www.angiodetect.co.uk), perhaps a dynamic picture of parasite distribution will emerge to guide us all. And who knows, as Kirk and others (2014) suggest, this evidence base could help to target intervention using the effective anthelmintic drugs now available for treatment and/or prevention (Conboy 2004, Willesen and others 2007, Schnyder and others 2009, Boehm and others 2014), to cool down some of the observed Angiostrongylus hotspots. That would constitute an impressively rapid and measured response to an emerging disease threat, led by sharp practitioners on the ground, with wider support from researchers and industry.…”
mentioning
confidence: 98%
“…Or perhaps something in between: a parasite found here and there, genuinely common and important in some areas and less so in others? The paper by Kirk and others (2014), summarised on p 118 of this issue of Veterinary Record , makes a valiant attempt to provide up-to-date answers, with interesting results. Veterinary practices were asked to retrospectively report the number of recent cases of angiostrongylosis, and an impressive number replied.…”
mentioning
confidence: 99%
“…THE article by Kirk and others (2014) and the corresponding editorial by Morgan (2014) on the apparent changing distribution of Angiostrongylus vasorum in the UK are of particular interest to me and I would like to make a few comments and one correction.…”
mentioning
confidence: 99%